Aspects of the nitrogen metabolism of sheep with special reference to the rumen - Van Niekerk, A. I.(Andre Isak) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1965.